Stock Market Reaction to Accounting Information of Listed Pharmaceutical Companies in Nigeria - Akani; Dike Stephen; Wobo; Henry Orowhuo (Formosa Journal of Multidisciplinary Research, 2023)
The aim of this study was to investigate the effect of accounting information on stock market reaction of quoted pharmaceutical companies in Nigeria by determining whether there is a significant relationship between accounting information and stock market reaction using 2009 to 2014 secondary data collected from the Nigeria Stock Exchange office in Port Harcourt, Rivers State, Nigeria. An ex post facto research design was appropriately adopted to address the objective of the study. Because of the research design adopted, a multiple regression analysis was employed to test the hypothesis raised in the study. The independent variable, which is accounting information, is measured as earnings per share (EPS) and book value per share (BVS), while the dependent variable, which is stock market reaction, is measured as stock price. The results obtained suggest that there is no statistically significant relationship between accounting information and stock market reaction; drawing on this finding, we concluded that accounting information has no significant effect on stock market reaction. Based on this finding, we recommend that sound and specific guidelines on accounting information should be issued by the Financial Reporting Council of Nigeria (FRCN) and the Security and Exchange Commission (SEC) so as to increase the relevance of accounting information of quoted companies.